Variability of pod trichome and agronomic characters of several soybean genotypes - M. MUCHLISH ADIE; AYDA KRISNAWATI (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Adie MM, Krisnawati A. 2017. Variability of pod trichome and agronomic characters of several soybean genotypes. Biodiversitas 18: 416-421. Trichome potentially act as a plant defense against soybean pod feeders, hence, the identification of trichome variability on soybean pod becomes increasingly important. A total of 150 soybean genotypes was identified for their pod trichome length and density. The experiment was conducted from February to June 2014. All soybean genotypes were planted in Muneng Research Station, Probolinggo (Indonesia). Identification of trichome length and density was performed in Laboratory of Biology, Malang State University. Soybean pods were taken from the third nodes at R7 stage. Soybean yield, pod trichome length and density were grouped using cluster analysis. The days to maturity varied from 72 to 83 days (average 77 days), 100 seed weight ranged from 12.50 to 23.50 g (average 16.50 g), seed yield ranged from 1.51 to 4.28 t/ha (average 2.90 t/ha), pod trichome length varied from 56.9 to 176.5 Âµm (average 112.8 Âµm), and trichome density ranged from 12 to 59 per 4 mm2 (average 27.64 per 4 mm2). Cluster analysis on 150 genotypes based on yield, trichome length, and trichome density classified soybean genotypes into five major groups. The first group consisted of 61 genotypes, and was characterized by sparse trichome. Cluster II consisted of genotypes with short trichome, whereas cluster III was characterized by medium trichome length and trichome density. Cluster IV and V, each consisted of six genotypes, and was characterized by dense and longer trichome, respectively. G511H/Arg//Arg///Arg///Arg-19-7 was the most densely pubescent genotype, while G511H/Anjasmoro//Anjasmoro-5-6 was the genotype with the longest trichome. These genotypes could be potentially be used as gene sources for further improvement of trichome length or trichome density in soybean varietal production.Keywords: Density, Glycine max, length, trichome